(untitled) (Orinoquia, 2018)
This experiment evaluated the effect of the supplementation of vitamin C on some productive and hematological parameters of cachama blanca submitted to acute hypoxia. 72 juveniles (30 ± 4.76 g) were used. They were fed ad libitum during 30 days with a diet of 32% of protein and different levels of vitamin C as follows: T1:0 mg/kg; T2:100 mg/kg; T3:200mg/kg; T4:400 mg/kg; T5:800 mg/kg; T6:1600 mg/kg. On day 30 the animals were sujected to aerial exposition during 60 seconds and returned to the water. Blood samples were taken at 5, 30, 60 and 360 minutes, to determine hematocrit, hemoglobin, cell count (red and white), leukocytes differential count, mean corpuscular volume, (MCV), mean corpuscular hemoglobin (MCH) and mean corpuscular hemoglobin concentration (MCHC). All animals were weighted to calculate weight growth (WG), specific growth rate (SGR), and relative growth (RG). Finally, survival rate was determined. The data were analyzed using variance analysis (ANOVA) and the means were compared using the Tukey’s test (5%). There were significant differences for WG, SGR, RG. T2 had the best parameters. The number of leukocytes was significatively higher in T5 in all sampling times. There were significative differences for monocytes among T1 and T4, and T5 and T6 in the first sampling, while for the basophils, lymphocytes, neutrophils and eosinophils there were not any differences among treatments or sampling times. Survival was 100% in all treatments. The results sugest that the supplementation with vitamine C in the diet could favour the growth of the species (WG, SGR, RG), but that excesive levels (1600 mg/kg) could have adverse effects on these parameter. On the other hand, although there were significative differences among treatments in the number of leukocytes and the percentage of monocytes, the hematological parameters evaluated, remained constant in relation to the condition of acute hypoxia, independently of the level of vitamin consumption.